N-n-Butyl Haloperidol Iodide Ameliorates Cardiomyocytes Hypoxia/Reoxygenation Injury by Extracellular Calcium-Dependent and -Independent Mechanisms. (12th November 2013) - Zhang, Yanmei; Chen, Gaoyong; Zhong, Shuping; Zheng, Fuchun; Gao, Fenfei; Chen, Yicun; Huang, Zhanqin; Cai, Wenfeng; Li, Weiqiu; Liu, Xingping; Zheng, Yanshan; Xu, Han; et al.
Abstract : N -n-butyl haloperidol iodide (F2 ) has been shown to antagonize myocardial ischemia/reperfusion injury by blocking calcium channels. This study explores the biological functions of ERK pathway in cardiomyocytes hypoxia/reoxygenation injury and clarifies the mechanisms by which F2 ameliorates cardiomyocytes hypoxia/reoxygenation injury through the extracellular-calcium-dependent and -independent ERK1/2-related pathways. In extracellularcalcium-containing hypoxia/reoxygenation cardiomyocytes, PKC α and ERK1/2 were activated, Egr-1 protein level and cTnI leakage increased, and cell viability decreased. The ERK1/2 inhibitors suppressed extracellular-calcium-containing-hypoxia/reoxygenation-induced Egr-1 overexpression and cardiomyocytes injury. PKC α inhibitor downregulated extracellularcalcium-containing-hypoxia/reoxygenation-induced increase in p-ERK1/2 and Egr-1 expression. F2 downregulated hypoxia/reoxygenation-induced elevation of p-PKC α, p-ERK1/2, and Egr-1 expression and inhibited cardiomyocytes damage. The ERK1/2 and PKC α activators antagonized F2 's effects. In extracellular-calcium-free-hypoxia/reoxygenation cardiomyocytes, ERK1/2 was activated, LDH and cTnI leakage increased, and cell viability decreased. F2 and ERK1/2 inhibitors antagonized extracellular-calcium-free-hypoxia/reoxygenation-induced ERK1/2 activation and suppressed cardiomyocytes damage. The ERK1/2 activator antagonized F2 's above effects. F2 had no effect on cardiomyocyte cAMP content or PKA and Egr-1 expression. Altogether, ERK activation in extracellular-calcium-containing and extracellular-calcium-free hypoxia/reoxygenation leads to cardiomyocytes damage. F2 may ameliorate cardiomyocytes hypoxia/reoxygenation injury by regulating the extracellular-calcium-dependent PKC α /ERK1/2/Egr-1 pathway and through the extracellular-calcium-independent ERK1/2 activation independently of the cAMP/PKA pathway or Egr-1 overexpression.